2017
DOI: 10.1001/jamaneurol.2017.1133
|View full text |Cite|
|
Sign up to set email alerts
|

Zolpidem for the Treatment of Neurologic Disorders

Abstract: IMPORTANCE Given its selective action on the ω1 subtype of the γ-aminobutyric acid A receptor, zolpidem tartrate presents a potential treatment mechanism for other neurologic disorders.OBJECTIVE To synthesize studies that used zolpidem to treat neurologic disorders.EVIDENCE REVIEW Eligibility criteria included any published English-language article that examined the use of zolpidem for noninsomnia neurologic disorders in humans for all dates up to March 20, 2015. Searched databases included PubMed, Scopus, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 63 publications
0
52
0
Order By: Relevance
“…is transient counterintuitive effect of zolpidem, a commonly used hypnotic, has been observed in many people with a variety of neurological disorders. While this effect has been well documented in the literature, much still remains to be understood [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is transient counterintuitive effect of zolpidem, a commonly used hypnotic, has been observed in many people with a variety of neurological disorders. While this effect has been well documented in the literature, much still remains to be understood [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there have been many reports where zolpidem has been used to treat a variety of neurological disorders of consciousness [5][6][7][8][9][10]. In a systematic review, Bomalaski and colleagues discussed the literature regarding the potential of zolpidem to treat a variety of neurological disorders and concluded that more research is needed to interrogate the complex underlying neurophysiological mechanisms involved and in order to understand zolpidem's usefulness as a therapeutic drug [11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a single prior report published more than two decades ago speculated that zolpidem would not be efficacious for PD, based on the limited clinical experience with the drug at the time, without specific consideration for cognition (Lavoisy and Marsac, 1997). However, recent publications demonstrate Zolpidem’s ability to treat a large variety of neurologic disorders, most often related to movement disorders and disorders of consciousness, and suggest zolpidem induces transient effects on UPDRS (Bomalaski et al, 2017). Of note, several cross-sectional reports have raised concerns for increased risk of reversible dementia or Alzheimer’s diseases in the general population when exposed to zolpidem (Shih et al, 2015; Lee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact there are some reports of development of periodic limb movement during zolpidem treatment especially in elderly females [24]. On the other hand, zolpidem has been found to be effective in a variety of movement disorders [25].…”
Section: Discussionmentioning
confidence: 99%